Trước tiên để dãy số này thành quy luật thì tớ xin phép sửa lại 1 thành 1/2 nhé
A = \(\frac{2^{ }}{2^2}\)+ \(\frac{3}{2^3}\)+ \(\frac{4}{2^4}\)+ ... + \(\frac{100}{2^{100}}\)
2A = 1 + \(\frac{3}{2^2}\)+ \(\frac{4}{2^3}+...+\frac{100}{2^{99}}\)
2A - A = A = 1 +\(\frac{1}{2^2}+\frac{1}{2^3}+\frac{1}{2^4}+...+\frac{1}{2^{99}}-\frac{100}{2^{100}}\)
2A = 2 + \(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{98}}-\frac{100}{2^{99}}\)
2A - A = A = \(1+\frac{1}{2}-\frac{99}{2^{99}}+\frac{100}{2^{100}}\)